Analysis of the Implementation of Islamic Boarding School Accounting in Preparing and Presenting Financial Reports at Tarbiyah Takalar Islamic Boarding School Middle School - Nur Fadillah Safitri; Muryani Arsal; Mira, Mira (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this research is a descriptive qualitative type of research with the aim of finding out the analysis of the implementation of Islamic boarding school accounting in the preparation and presentation of financial reports at the Tarbiyah Takalar Islamic Boarding School Middle School. This sample was taken from Tarbiyah Takalar Islamic Boarding School Middle School. The type of data used in this research is descriptive qualitative data obtained from interviews related to the problem under study. Data collection was carried out by interviews, observation and documentation. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research uses narrative methods, data reduction, data presentation and drawing conclusions. Based on the results of data research using interviews regarding the analysis of the implementation of Islamic boarding school accounting in the preparation and presentation of financial reports at Tarbiyah Takalar Islamic Boarding School Middle School which has been discussed in the previous chapter, the author draws an important conclusion, namely that the financial reports of Tarbiyah Takalar Islamic Boarding School Middle School are not in accordance with Islamic boarding school accounting guidelines. have not identified the assets, liabilities and net assets owned by the Islamic boarding school and the preparation and presentation of the financial reports of the Tarbiyah Takalar Islamic Boarding School are not in accordance with ISAK 35.